Volume 16 - A., Anderson (International Journal of Psychosocial Rehabilitation, 2012)
Motivational Interviewing (MI) is an evidence-based clinical intervention that has shown positive outcomes for individuals with co-occurring serious mental illness and substance use disorders. Many of these individuals are similar to those served by Assertive Community Treatment (ACT) teams, highlighting that MI is an important intervention and a beneficial modality to be used within ACT teams. This article examines areas of treatment (assertive engagement, Integrated Dual Disorder Treatment and person- centered planning) which both utilize MI techniques and are considered an integral part of ACT services. These three areas of treatment are also assessed within the Tool for Measurement of Assertive Community Treatment (TMACT), an instrument used to assess fidelity to the ACT model. Lessons learned from the implementation, training and fidelity measurement of ACT teams in Washington State and recommendations for future MI implementation within ACT teams are described. ces.